ANALYSIS OF THE EFFECTIVENESS OF THE CAMPAIGN OF THE SINGLE CANDIDATE OF THE REGIONAL HEAD IN INFLUENCING THE VOTE (STUDY OF THE ELECTION OF REGENT AND DEPUTY REGENT OF SERDANG BEDAGAI) - Ewin Saputra Saragih; Marzuki Marzuki; Ibnu Affan (Jurnal Ilmiah METADATA, 2025)
Elections play a strategic role in building democracy and guaranteeing the rights of the people. One of the main features of democracy is elections that face various challenges in the process, especially in this case regarding the effectiveness of the campaign of a single candidate for regional heads in influencing votes. The legal arrangements for the election campaign for Regional Heads with a single candidate are regulated in the General Election Commission Regulation Number 15 of 2023 concerning General Election Campaigns which regulates the General Election Campaign which includes, the implementation of the Campaign, General Election Campaign materials, Campaign methods, news and broadcasting, Election Campaigns, prohibition of Election campaigns, coordination with ministries/local government agencies, the Indonesian National Army, and the Indonesian National Police in the implementation of General Elections, socialization and political education. The implementation of the Regional Head Election campaign with a single candidate is an important stage to introduce regional head candidates to the public and convince voters to vote for them.